Pemberdayaan Perempuan dalam Pembangunan Ekonomi di Karawang - Rahma Andita Sari; Rini Sulastri (Gunung Djati Conference Series, 2024)
Women's empowerment in the context of economic development has a central role in creating inclusiveness and sustainable growth. In Karawang, the role of women's entrepreneurship in economic development is an important issue that requires in-depth understanding. This research aims to measure the extent to which women's entrepreneurship can be an instrument of empowerment in increasing economic development in this area. This research methodology uses a qualitative approach, with data collection through in-depth interviews and surveys. Respondents consisted of women involved in entrepreneurial activities in various economic sectors in Karawang. The results of this research show that although women in Karawang face a number of obstacles in entering the world of entrepreneurship, they have great potential to contribute to local economic development. Empowering women through entrepreneurship can improve women's living standards and encourage inclusive economic growth. Empowerment programs that support women's entrepreneurship are identified as key to achieving better outcomes.